Impacts of COVID-19 on people's food security: Foundations for a more resilient food system - Béné, Christophe; Bakker, Deborah; Sonneveld, Anne; Chavarro, Monica; Even, Brice; Melo, Jenny (2021)
Christophe Béné (The Alliance Bioversity International – CIAT) Deborah Bakker and Anne Sonneveld (Wageningen University and Research) Monica Chavarro, Brice Even and Jenny Melo (The Alliance Bioversity International – CIAT Food systems lessons from COVID-19: From understanding fragilities to building resilience Co-Organized by IFPRI and the CGIAR COVID-19 Hub MAR 2, 2021 - 09:30 AM TO 11:00 AM EST